ANALISIS TITIK PULANG POKOK USAHA KOPI JAHE PADA IKM SAL-HAN DI KOTA PALU - Hamsir, Hardin M.; Antara, Made; Howara, Dafina (AGROTEKBIS, 2018)
This study aims to find out the Analysis of break even points of ginger coffee business at IKM Sal-Han in Palu City. The research was conducted at IKM Sal-Han jl. Sis-Aljufri No. 48 Palu in February 2017 to March 2017. Respondents in this study are the leader or owner of SMI Sal-Han and two employees of production. Analysis tool used in this research is Break Even Point. The results showed that break even point for ginger coffee packing product 200 g reached on production volume as much as 51 packaging with price Rp 25.000/packaging then the value of sale at the break even point of  Rp 1,275,000 /3 months, For ginger coffee packing product 300 g is achieved at 8 production volume at the price of Rp 45.000 / packaging then the value of sale at the break even point counted of Rp 3,600,000 / 3 months, for ginger coffee packing product 400 g reached on The production volume of 11 with the price of Rp 50.000/packaging then the value of sales at the break even point counted of  Rp 550,000 / 3 months and for the production of ginger coffee packing 500 g achieved on the production volume of 6 With the price of 50.000/packaging then the value of sales at the break even point of return counted of Rp 300,000 / 3 months.